Promoting The Tourism Sector as a Tool to Achieving The Local Development In Mila City - SADIKI, SOUADE (Milev Journal of Research and Studies, 2015)
The tourism sector is the most important sectors of the moment ,due to the achievements of the great financial returns and they have a key role in the national economic and social development and local, is a strategic alternative to move from dependence on sources of depleted wealth ,and they also contribute to alleviate a lot of economic problems, and that is seeking to use them to promote its economy and achieve regional balance ;with decoding the isolation of the different mandates and openness to each other for the sake of development, and the state of Mila among states that have huge tourist resources can be used to make the further operation of various economic activities and increase revenues and job creation benefits all members of society and thus participate in local development of the state.